CRL network optimization program, Version CRL1 - Bandler, John W.; Rizoniko-Popovic, Jadranka (Communications Research Laboratory, 1973)
This program analyzes and optimizes certain electrical networks arranged as a cascade of two-ports such as microwave filters and allpass networks. John W. Bandler was a member of the Communications Research Laboratory from 1970 to 1973, leaving to form the Research Group on Simulation, Optimization and Control.
Report and program package produced by John W. Bandler and Jadranka Rizoniko-Popovic. Program package is written in FORTRAN IV. This work is licensed under a Creative Commons Attribution-Non-Commercial-No-Derivatives 4.0 International License.
Keywords: network optimization; computer-aided design